Weft, Warp, and Weave: The Intricate Tapestry of Calcium Channels Regulating T Lymphocyte Function - Omilusik, Kyla D.; Nohara, Lilian L.; Stanwood, Shawna; Jefferies, Wilfred (Frontiers in Immunology, 2013)
Calcium (Ca2+) is a universal second messenger important for T lymphocyte homeostasis, activation, proliferation, differentiation and apoptosis. The events surrounding Ca2+ mobilization in lymphocytes are tightly regulated and involve the coordination of diverse ion channels, membrane receptors and signalling molecules. A mechanism termed store-operated Ca2+ entry (SOCE), causes depletion of endoplasmic reticulum (ER) Ca2+ stores following T cell receptor (TCR) engagement and triggers a sustained influx of extracellular Ca2+ through Ca2+ release-activated Ca2+ (CRAC) channels in the plasma membrane. The ER Ca2+ sensing molecule, stromal interaction molecule 1 (STIM1), and a pore-forming plasma membrane protein, ORAI1, have been identified as important mediators of SOCE. Here, we review the role of several additional families of Ca2+ channels expressed on the plasma membrane of T cells that likely contribute to Ca2+ influx following TCR engagement, particularly highlighting an important role for voltage-dependent Ca2+ channels (CaV) in T lymphocyte biology.